UPI community services actions to combat stunting in Ciherang Village, Cianjur - Fauziah Fauziah; Ilham Firdaus; Santi Sukmawati (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Stunting is a significant nutritional problem and is currently prevalent in Indonesia. The problem of stunting will have a negative impact on the physical growth and brain development of children so that it can affect the quality of human resources, worsen intergenerational poverty, and have a negative impact on the country's economic growth, so this problem must be prevented and addressed immediately. This community service aims to increase public awareness and education about preventing stunting through Kuliah Kerja Nyata (KKN) program in Ciherang Village, Cianjur. The community service carried out by KKN-T students from the Indonesian Education University, through seminars and talk shows with the theme "Ciherang, Zero Stunting" focused on emphasizing public understanding of stunting through seminars and talk shows. The enthusiasm of the participants, especially Posyandu cadres, pregnant women, and adolescents, showed an increase in understanding of the importance of nutrition and a healthy lifestyle. This activity succeeded in making a positive contribution in supporting the program to accelerate the reduction of stunting at the local level. The high enthusiasm of the participants showed the success of the program in providing the information and skills needed to detect stunting early. Through this initiative, UPI KKN students play an active role in educating the community and encouraging real action to combat stunting, which is expected to reduce the prevalence of stunting in Ciherang Village.   Abstrak Stunting merupakan masalah gizi yang signifikan dan banyak terjadi di Indonesia saat ini. Masalah stunting akan berdampak buruk pada pertumbuhan fisik dan perkembangan otak anak sehingga dapat memengaruhi kualitas sumber daya manusia, memperburuk kemiskinan antar generasi, dan berdampak negatif pada pertumbuhan ekonomi negara, sehingga masalah ini harus segera dicegah dan ditangani. Pengabdian ini bertujuan untuk meningkatkan kesadaran dan edukasi masyarakat tentang pencegahan stunting melalui program Kuliah Kerja Nyata (KKN) di Desa Ciherang, Cianjur. Pengabdian yang dilaksanakan oleh mahasiswa KKN-T Universitas Pendidikan Indonesia, melalui seminar dan talkshow bertema "Ciherang, Zero Stunting" berfokus pada penekanan pemahaman masyarakat mengenai stunting melalui seminar dan talkshow. Antusiasme peserta, terutama kader posyandu, ibu hamil, dan remaja, yang menunjukkan peningkatan pemahaman tentang pentingnya gizi dan pola hidup sehat. Kegiatan ini berhasil memberikan kontribusi positif dalam mendukung program percepatan penurunan stunting di tingkat lokal. Tingginya antusiasme peserta menunjukkan keberhasilan program dalam memberikan informasi dan keterampilan yang diperlukan untuk mendeteksi dini stunting. Melalui inisiatif ini, mahasiswa KKN UPI berperan aktif dalam edukasi masyarakat dan mendorong tindakan nyata untuk melawan stunting, yang diharapkan dapat menurunkan prevalensi stunting di Desa Ciherang. Kata Kunci: pendidikan masyarakat; pengabdian kepada masyarakat; stunting